# Show $a^p \equiv b^p \mod p^2$

I am looking for a hint on this problem:

Suppose $a,b\in\mathbb{N}$ such that $\gcd\{ab,p\}=1$ for a prime $p$. Show that if $a^p\equiv b^p \pmod p$, then we have: $$a^p \equiv b^p \pmod {p^2}.$$

I have noted that $a,b$ are necessarily coprime to $p$ already, and Fermat's little theorem ($x^p\equiv x \pmod p$), but I do not see how I should apply it in this case if at all.

Any hints are appreciated!

• Do you mean $\gcd(ab,p)=1$? – mysatellite Dec 18 '15 at 3:44
• Hint: prove first that $a \equiv b \mod p$. The condition $(ab,p) = 1$ is useless, and $a$ and $b$ can be any integers. – darij grinberg Dec 18 '15 at 3:44
• Oh yes, I will edit that in a second, it is just short form that a professor had used. – anakhro Dec 18 '15 at 3:44
• @darijgrinberg It follows from Fermat's little theorem easily that $a\equiv b$ (mod p). However, I am still stuck on where that leads me. Is there another tiny nudge you can give me in the right direction? – anakhro Dec 18 '15 at 3:47

Fermat's Little theorem should help you show $a\equiv b(\text{mod }p)$, at which point you have $a=b+pk$ for some $k\in\mathbb{Z}$. An application of the binomial theorem from here could give you the result you seek.

• Would that be an application of the binomial theorem to $(a-b)^p$, by any chance? – anakhro Dec 18 '15 at 4:05
• I think it might be easier to apply it to $a^p$, but you would get the same result using $(a-b)^p$. – Mb123 Dec 18 '15 at 4:06
• Thank you, that is sufficient! – anakhro Dec 18 '15 at 4:08
• Alternatively, $a^p - b^p = \left(a-b\right)\left(a^{p-1} + a^{p-2} b + \cdots + b^{p-1}\right)$. Now, you only need to check that the second parenthesized factor is divisible by $p$. – darij grinberg Dec 18 '15 at 4:22
• @darijgrinberg I can't see any relatively straightforward way of doing so? – Steven Stadnicki Dec 18 '15 at 4:23

You could generalize this further. Here is one of the Lifting the Exponent Lemmas (LTE):

Define $\upsilon_p(a)$ to be the exponent of the largest prime power of $p$ that divides $a$.

If $a,b\in\mathbb Z$, $n\in\mathbb Z^+$, $a\equiv b\not\equiv 0\pmod{p}$, then $$\upsilon_p\left(a^n-b^n\right)=\upsilon_p(a-b)+\upsilon_p(n)$$

In your case, by Fermat's Little theorem $a^p\equiv b^p\not\equiv 0\pmod{p}\iff a\equiv b\not\equiv 0\pmod{p}$, therefore $$\upsilon_p\left(a^p-b^p\right)=\upsilon_p(a-b)+\upsilon_p(p)=\upsilon_p(a-b)+1$$

Therefore $p^2\mid a^p-b^p$.

• I like this a lot! Thanks! – anakhro Dec 19 '15 at 3:24
• The LTE Lemma I cited only holds for odd $p$. I only proved your problem for odd primes $p$. – user236182 Dec 26 '15 at 5:57